Інтегрування одного класу систем диференціальних рівнянь за допомогою контурного інтеграла - Іванюк, М.М. (Український математичний журнал, 1995)
For systems ofq linear differential equations ofnth order with polynomial matrix coefficients, a fundamental family of formal solutions defined in a certain sector of a complex plane is constructed by using the Laplace contour integral. For large positive values of an independent variable, the asymptotic representations of indicated solutions are obtained.